Growth performance and carcass characteristics of lambs raised on varying proportion of roughage and concentrate - KARIM, S A; RAWAT, P S (The Indian Journal of Animal Sciences, 2013)
This study was conducted on native andctossbred weaner lambs to assess their sgowth resqonse and carcass traits under intensive feeding for 90 days on composite rations having 35 (G1),45 (G2), 55 (G3) and 65 (G4) % Zizyphus nummularia leaves in the diet. Initial body weights were similar in the 4 groups, The final weights and ADG were higher (P